COVID-19 in der Schwangerschaft: Ursache für eine intrakranielle Blutung bei einem Frühgeborenen? - Klüßendorf, Anne; Richter, Manuela F.; Webermann, Santje; Schild, Ralf L.; Morfeld, Christine A. (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Maternity clinics are increasingly being confronted with pregnant women suffering from Covid-19. This poses great challenges for obstetricians, since some questions have not yet been adequately researched scientifically. Not much is known about COVID-19 during pregnancy and its effects on the unborn and newborn child.
Keywords: anamnestische Schwangerschaftsrisiken; fetale Wachstumsrestriktion; Neonatalperiode; Frühgeburt; Infektion